Impact of the crosstalk between the PTEN and PAFR as well as PAFR and EGFR pathways in cancer - Anita Thyagarajan; Zaid Sirhan; Ravi P. Sahu (Exploration of Drug Science)
The integration between the tumor-suppressive and oncogenic signaling pathways controls various cellular activities of cancer cells, including cell growth and apoptosis. While the activation of oncogenes fuels cancer progression and escape mechanisms, tumor suppressors regulate and counterbalance the negative effects of oncogenic signaling. Notably, phosphatase and tensin homolog (PTEN) constitute one of the important family members of tumor suppressor genes, which play critical roles in regulating the activities of tumor cells. Thus, an impaired, mutated, or loss of PTEN is associated with low survival or high tumor recurrence rates in cancer patients. Importantly, high tumor expression of a G-protein coupled platelet-activating factor-receptor (PAFR) is associated with increased tumor progression as well as decreased overall survival and poor prognosis in malignancies such as non-small cell lung cancer (NSCLC). Along similar lines, overactivation or mutations in epidermal growth factor receptor (EGFR) signaling are detected in various human malignancies and associated with poor prognosis. The goal of the current minireview was to highlight the significance of the mechanistic insights between the PTEN and PAFR as well as the PAFR and EGFR pathways in impacting cancer growth and/or efficacy of therapeutic agents in experimental model systems.